Interior Environment Enhancing Child Development - Nipattha Noiprawa; Nopadon Sahachaisaeree (My University, 2017)
The environment has been a crucial factor in determining the effectiveness of medical treatment, especially for mentally related disorders. The study uses the autistic treatment environment as a case study to examine relevant environmental factors supporting the learning process of autistic children towards an environmental design model, the improvement in behaviour, and be able to stabilize the patient's emotions. Results from the study are useful for the prognostic study of autism. The final modelling could be applied as a part of special education programs to extenuate behavioural and emotional disorders and to improve the social skills of autistic children.
Keywords: Social Skills; Child Therapy and Development